A comparison of two numerical relay low impedance restricted earth fault algorithms in power transformer - Nimtaj, Babak; Mahmoudi, Amin; Palizban, Omid; Kahourzade, Solmaz (2011 8th International Conference on Electrical Engineering/Electronics, Computer, Telecommunications and Information Technology, 2011)
Low impedance restricted earth fault protection is one of the protection functions to protect the transformer winding with earthed star point. This paper presents a critical comparison of restricted earth fault between General Electric algorithm and Siemens Algorithm. Advantages and disadvantages of selected algorithms are investigated based on speed, sensitivity and security. The relay operation characteristic curves and restraint currents for each of algorithms are simulated by MATLAB SIMULINK.